2017
DOI: 10.1007/s00520-017-4011-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two types of palliative sedation therapy defined using intervention protocols: proportional vs. deep sedation

Abstract: The two types of intervention protocol well reflected the treatment intention and expected outcomes. Further, large-scale cohort studies are promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 34 publications
0
58
0
5
Order By: Relevance
“…Studies were conducted in Belgium, 25,26 Italy, 27,28 Japan, 29,30 The Netherlands, 31,32 Colombia, 33 and Mexico. 34 Two articles pertain to the same study, 31,32 so results have been reported as one study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were conducted in Belgium, 25,26 Italy, 27,28 Japan, 29,30 The Netherlands, 31,32 Colombia, 33 and Mexico. 34 Two articles pertain to the same study, 31,32 so results have been reported as one study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Strengths identified in the articles are recruitment across several settings, data collected during a year, 29e32 and assessment of specific outcomes and measurement times. 29 Some of the limitations identified in the articles include a small sample size; 26,29,33,34 lack of clarity about the assessment tools used, 26,27,29,30,33,34 timing, and follow-ups; 25 inability to ensure that study reports are truly comparable at baseline; 28 and lack of a uniform standardized protocol for sedation among settings. 30 Study designs used are longitudinal studies with follow-up lengths ranging from one to four months, 25,27,31,32 three observational studies, 28,33,34 two cohort studies, 29,30 and one mixed-method study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines and expert reviews recommend that sedatives should first be titrated to a minimal dose required to provide adequate palliation of suffering, rather than to continuously induce unconsciousness 71–74. As part of efforts to standardise end-of-life treatment, a reproducible protocol of proportional midazolam use has recently been proposed that reflects the treatment intention and expected outcome 71 75. However, it remains unknown when breathlessness should be considered non-responding to symptomatic treatment, and how best sedatives should be titrated to relieve persistent intractable breathlessness in particular.…”
Section: Current Evidence Supporting Treatment For Terminal Breathlesmentioning
confidence: 99%
“…In addition, recent studies on terminal agitation and death rattle have demonstrated the feasibility of RCTs in patients during the last days of life, if appropriate strategies are implemented 22 77 82. Strategies include, but are not limited to, the use of advance or proxy consent, standardisation of care programmes, the application of short observation periods and the use of clinically implemented outcomes 22 75 82. While an RCT is the gold standard for demonstrating the efficacy of medication, continuous recording of routinely collected data would also enable researchers to conduct non-randomised comparative studies among treatment modalities.…”
Section: Unanswered Research Questions In Terminal Breathlessnessmentioning
confidence: 99%